Penerapan Teknik What, Why, Where, Who, Hhen+How (5W+1H) dalam Meningkatkan Keterampilan Menulis Cerpen Siswa di Sekolah Menengah Kejuruan - Hasmar, Hasmar; Tumpu, Abu Bakar; Erniati, Erniati (Program Studi Pendidikan Bahasa dan Sastra Indonesia, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Islam Makassar, 2023)
This study aims to find out the Student Team Achievement Division (STAD) model in Junior High This study aims to determine the application of What, Why, Where, Who, Hhen + How (5W + 1H) Techniques in Improving Students' Short Story Writing Skills in Vocational High Schools. The approach used in this study uses a qualitative approach with a type of classroom action research. This method is expected to be able to improve the ability to write short stories at vocational high schools at SMK Darussalam in Makassar. The data collection techniques used in this study are test techniques and non-test techniques. The test technique is used to find out how much the level of students' ability to write short stories through the 5W + 1H technique. H asil research and discussion can be concluded that the ability to write short stories for class X vocational high school (SMK) students in Makassar has participated in learning to write short stories through the 5W + 1H technique has increased. The results were obtained from the average score of the short story writing class cycle I of 78.42 and cycle II the average score of the class of 89.84 and was included in the good category.